Economic Adjustment and Reform in Low-Income Countries (ESAF Review Background Papers) - Schadler, Susan (International Monetary Fund, 1999)
The Enhanced Structural Adjustment Facility (ESAF) is the cenerpiece of the International Monetary Fund's strategy to provide assistance on concessional terms to low-income member countries that are undertaking important macroeconomic adjustment and stuctural reforms. By February 1999, a total of SDR 7 billion (about USD 9 billion) had been distributed under 79 ESAF arrangements to 51 developing countries. Edited by Hugh Bredenkamp and Susan Schadler, this volume features internal IMF staff assessments of the ESAF and provides an historical account of policies implemented and outcomes achieved under ESAF- supported programs.